Sistema de espaços livres no bairro Buritis, em Belo Horizonte (MG) - Mirelli Borges Medeiros (2016)
Brazils increasing urbanization in the twentieth century was caused by the migration of rural population to the cities causing the expansion of built spaces and the reduction of public and private open spaces. Some cities have expanded by incorporating rural areas and becoming completely urbanized. The urban landscapes are in constant mutation where built spaces take precedence over public and private open spaces thus affecting the permeability of the soil, air quality and mobility in general, a negative effect on the quality of urban life. This work investigates the relationship between public and private open spaces and built spaces focusing on how they are used as a system by local population. The object of study is the Buritis neighborhood in Belo Horizonte, Minas Gerais, because it is one of the last land subdivisions approved in the capital. Through bibliographic references, analysis of urban planning and environmental laws in effect as well as field research, it was possible to assess Buritis and the Municipal Park Aggeo Pio Sobrinho's urban development. This work employed theoretical concepts of Urban Morphology through which the current urban form is understood as a product of human intervention over the physical and biological environment in a given period of time. Through a quantitative and qualitative analysis of the existing open spaces, it was possible to conclude that, despite the significant green space to inhabitant ratio, they are still not homogeneously and efficiently distributed. This work on the other hand proposes a possible system of open spaces based on a new perspective over their public and private qualities. The research is based upon a replicable methodology that identifies potentialities and deficiencies of existing public spaces. The study of the Buritis region can contribute to the discussion of the value of public open spaces in Belo Horizonte and in other contemporary cities.